(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to improve learning outcomes through Problem-Based Learning (PBL) on physical fitness material in vocational high school students. This research used the Classroom Action Research (CAR) method, consisting of two cycles, where each cycle includes planning, implementation, observation, and reflection stages. The subjects were 30 students of class XI DPB 2 at SMK Negeri 4 Jambi City. Data were collected through observation and written tests on physical fitness material. The research showed that Problem-Based Learning had a positive impact on Physical Education learning, especially on physical fitness material. In the first cycle, only 46.66% of students achieved the minimum completeness criteria (KKM) with scores ≥70. However, after improvements in the second cycle, the percentage of students achieving KKM increased to 86.66%. Besides improving learning outcomes, students also showed higher motivation and participation during the learning process. The use of the Problem-Based Learning model can enhance the effectiveness of physical fitness learning and provide more enjoyable and safe learning experiences for students. Physical Education teachers are expected to apply similar innovations in PE learning to improve students’ thinking patterns and interest in sports. This study includes 2 tables, 20 references, and observational instruments.